2019
DOI: 10.1001/jamasurg.2018.3475
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided Surgery With Gallium 68 Dotatate for Patients With Neuroendocrine Tumors

Abstract: IMPORTANCE Neuroendocrine tumors (NETs) express somatostatin receptors, which can be targeted with radiolabeled peptides. In a variety of solid tumors, radioguided surgery (RGS) has been used to guide surgical resection. Gallium 68 (68 Ga) dota peptides have been shown to be more accurate than other radioisotopes for detecting NETs. A pilot study previously demonstrated the feasibility and safety of 68 Ga-dotatate RGS for patients with NETs. OBJECTIVE To evaluate what intraoperative techniques and thresholds d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Although laparoscopic resection of SBNEN has been reported 50 , 51 , we are in favour of laparotomy allowing for meticulous palpation of the entire small bowel and identification of frequently millimetre-sized intramural tumours not seen preoperatively on any imaging or endoscopy 52 , and optimal extent of lymphadenectomy (at least 8 lymph nodes) under consideration of intestinal-sparing principles 53 , 54 . Hand-held gamma probe surgery using gallium-68-labeled somatostatin analogues has been shown to be a promising adjunct for real-time detection of small metastatic deposits and primary tumours 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Although laparoscopic resection of SBNEN has been reported 50 , 51 , we are in favour of laparotomy allowing for meticulous palpation of the entire small bowel and identification of frequently millimetre-sized intramural tumours not seen preoperatively on any imaging or endoscopy 52 , and optimal extent of lymphadenectomy (at least 8 lymph nodes) under consideration of intestinal-sparing principles 53 , 54 . Hand-held gamma probe surgery using gallium-68-labeled somatostatin analogues has been shown to be a promising adjunct for real-time detection of small metastatic deposits and primary tumours 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that RGS combined with 68 Ga-DOTATATE in GEP-NET patients showed feasibilities in guiding the removal of lymph node metastasis and both intraoperative evaluation as well as establishing the correctness of surgical margins. In addition, it could also be valuable in the identification and removal of minor tumors that were invisible or not palpable in recurrent NET patients, in whom the surgical area is covered with scar tissue (82,83).…”
Section: Sstr-targeted Imaging In Pnetsmentioning
confidence: 99%
“…Mono-and multi-center clinical trials demonstrated benefits of SSTR targeted pre-therapeutic imaging and radiotherapy in terms of patient management efficiency, efficacy, safety, and survival [12][13][14]. [ 68 Ga]Ga-SST was found valuable not only for pre-operative assessment of resectable lesions and multiple unresectable lesions but also for intraoperative radio-guided resection [15,16]. [ 68 Ga]Ga-SST/PET is also efficient tool for the scheduling of the treatment combining long-acting somatostatin analogue (SSA) therapy and endoradiotherapy [17] since the amount of the administered peptide influences the biodistribution pattern and might enhance lesion uptake while reducing uptake in the healthy tissue and organs with physiological expression of the target [2,18,19].…”
Section: Targeting Sstr On Neuroendocrine Neoplasmsmentioning
confidence: 99%
“…[ 68 Ga]Ga-SST PET uptake heterogeneity determined based on intratumoral textural features predicted endoradiotherapy outcome more accurately than SUV max [105]. A threshold of 2.5-4.46 or higher for probe TBR was found a sensitive parameter for guided surgical resection ( Figure 4) [15,16]. The tumor SUV max reaches plateau 5 min post injection and remains unchanged within the range of 5-90 min [106] providing freedom of the examination logistics.…”
Section: Impact Of Sst Radiopharmaceuticals On Patient Treatment Manamentioning
confidence: 99%